AuNP/Chitosan Nanocomposites Synthesized through Plasma Induced Liquid Chemistry and Their Applications in Photothermal Induced Bacteria Eradication - Zhijun Guo; Dan Sun; Xian Zhou; Huan Xu; Yizhou Huang; Chenglin Chu; Baolong Shen (MDPI AG, 2022)
In this work, a facile direct current atmospheric pressure micro-plasma (APM) technology was deployed for the synthesis of functional gold nanoparticle/chitosan (AuNP/CS) nanocomposites for the first time. Different experimental parameters, such as metal salt precursor concentration and chitosan viscosity, have been investigated to understand their effects on the resulting nanocomposite structures and properties. The nanocomposites were fully characterized using a wide range of material characterization techniques such as UV-vis, transmission electron microscope (TEM), Fourier transform infrared (FTIR) spectra and X-ray photoelectron spectroscopy (XPS) analyses. Potential reaction pathways have been proposed for the nanocomposite synthesis process. Finally, potential of the synthesized nanocomposites towards photothermal conversion and bacteria eradiation applications has been demonstrated. The results show that APM is a facile, rapid and versatile technique for the synthesis of AuNP/CS functional nanocomposites. Through this work, a more in-depth understanding of the multi-phase system (consisting of gas, plasma, liquid and solid) has been established and such understanding could shine a light on the future design and fabrication of new functional nanocomposites deploying the APM technique.